Predictors of Lesions Contiguity and Transmurality in Canine Ventricular Models After Catheter Ablation - El Hajjar, Abdel Hadi; Mekhael, Mario; Huang, Chao; Noujaim, Charbel; Zhang, Yichi; Kholmovski, Eugene; Ayoub, Tarek; Lim, Chan Ho; Marrouche, Nassir (Frontiers in Cardiovascular Medicine, 2022)
Background: Interlesion gaps and transmurality of lesions after catheter ablation can precipitate suboptimal efficacy. Aims: To assess predictors of acute transmural lesion formation and the interlesion distance threshold for creating a continuous, chronic scar after ventricular ablation. Methods: Ablation procedures were performed on 7 canines followed by LGE-MRI. Transmurality was assessed by 2 independent operators. Ablation parameters such as duration (s), power (W), temperature (C), contact force (CF) (g), were collected for each ablation point. After 7-12 weeks, LGE-MRI was performed, followed by euthanasia, and heart excision. Some lesions were created in pair. Lesion pairs were spaced 7-21 mm apart as measured by Electroanatomic mapping (EAM), with different operating parameters. We performed a logistic regression analysis to determine predictors of transmural lesion formation. Results: Eighty-one radiofrequency ablation were performed in total (33 in the Left ventricle (LV) and 48 in the Right ventricle (RV)). Higher CF was a significant predictor of transmural lesion formation (β=0.15, OR= 1.16, 95% CI [1.03 – 1.3], p=0.01), and lesions delivered in the RV were more frequently transmural than lesions delivered in the LV (β=-2.43, OR= 0.09, 95%CI [0.02 – 0.34], p<0.001). For the paired analysis, thirty-eight lesions were created contiguously: fourteen connected lesions and twenty-four unconnected lesions. EAM distance was significantly larger in unconnected lesions than connected lesions (16.17 +/-0.92 mm vs. 11.51 +/-0.68 mm respectively, p<0.05). We concluded that an interlesion distance of less than 10 mm is required to prevent gap formation. Average volumes in unconnected lesions (n=24) at the acute and chronic stages were 0.55 ± 0.11 cm3 and 0.20 ± 0.02 cm3, respectively. On average, lesion volumes were 64% (p<0.05) smaller at the chronic stage compared to the acute stage. Among connected lesions (n=14), we observed a volume of 1.19 ± 0.8 cm3 and 0.39 ± 0.15 cm3 at the acute and chronic stages, respectively. These connected lesions reduced in volume by 67% on average. Conclusion: To create contiguous scars on the ventricular endocardial surface, paired lesions should be spaced less than ten millimeters apart. Higher contact force should be used in ventricular ablation to create transmural lesions.